PERCEPTION AND AWARENESS ANALYSIS OF FINANCIAL TECHNOLOGY (FINTECH) SERVICES AMONGST THE EXPATRIATES IN THE UNITED ARAB EMIRATES - Aamir Shakir; Nitin Simha Vihari (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The objective of this study is to analyse the perception and awareness of the Expatriates and start-up businesses of the presence and value proposition of FinTech Services such as Payment/Banking, Lending and Crowdfunding in UAE. Data was collected using a survey-based questionnaire and respondents were chosen using convenient sampling method. Research design is a Cross-Sectional design. Data was collected between February to April 2020. The target audiences were Expats between the ages of 20-40 who have been living in UAE for at least 3 years. The level of awareness of most respondents in the FinTech services such a P2P lending; Robo Advising and Insurtech were fairly limited. The results discovered reflect a positive sign regarding the acceptance of these new FinTech services in UAE. From the findings, we can also notice that majority of the respondents are hoping for FinTech to be able to act as a secondary financing source apart from normal financing methods. And moreover, FinTech development in the UAE market could further increase business activities all throughout. Not many in depth studies on FinTech have been done across the world. In the context of UAE there were even lesser. This paper is one of its kinds in the region, which allows us to understand the awareness and perception of consumers towards technology and the financial industry using a broad spectrum of variables.